Case Report: Subtherapeutic Vancomycin and Meropenem Concentrations due to Augmented Renal Clearance in a Patient With Intracranial Infection Caused by Streptococcus intermedius - Fransson, Marcus; Helldén, Anders; Östholm Balkhed, Åse; Nezirević Dernroth, Dženeta; Ha, Maria; Haglund, Mats; Milos, Peter; Hanberger, Håkan; Kågedal, Bertil (Frontiers in Pharmacology, 2021)
Streptococcus intermedius occasionally causes brain abscesses that can be life-threatening, requiring prompt antibiotic and neurosurgical treatment. The source is often dental, and it may spread to the eye or the brain parenchyma. We report the case of a 34-year-old man with signs of apical periodontitis, endophthalmitis, and multiple brain abscesses caused by Streptococcus intermedius. Initial treatment with meropenem and vancomycin was unsuccessful due to subtherapeutic concentrations despite recommended dosages. Adequate concentrations could be reached only after increasing the dose of meropenem to 16 g/day and vancomycin to 1.5 g x 4. The patient exhibited high creatinine clearance consistent with augmented renal clearance, though iohexol and cystatin C clearances were normal. Plasma free vancomycin clearance followed that of creatinine. A one-day dose of trimethoprim-sulfamethoxazol led to an increase in serum creatinine and a fall in both creatinine and urea clearances. These results indicate that increased tubular secretion of the drugs was the cause of suboptimal antibiotic treatment. The patient eventually recovered but his left eye needed enucleation. Our case illustrates that augmented renal clearance can jeopardize the treatment of serious bacterial infections, and that high doses of antibiotics are needed to achieve therapeutic concentrations in such cases. The mechanisms for regulation of kidney tubular transporters of creatinine, urea, vancomycin, and meropenem in critically ill patients are discussed.